The use of physiological, anthropometric, and skill data to predict selection in a talent-identified junior volleyball squad - Gabbett, T.; Georgieff, B.; Domrow, N. (Journal of Sports Sciences, 2007)
The aim of this study was to determine whether physiological, anthropometric, and skill test results could discriminate between junior volleyball players of varying ability. Twenty-eight junior volleyball players competed for selection in a talent-identification volleyball programme. Participants underwent measurements of stature, standing reach stature, body mass, skinfold thickness, overhead medicine ball throw, vertical jump, spike jump, 5-m and 10-m speed, "T" test agility, maximal aerobic power, and passing, setting, serving, and spiking technique and accuracy. A discriminant analysis was conducted on the selected and non-selected groups to obtain a regression equation that could be used to predict selection in junior volleyball squads based on the dependent variables. Passing and serving technique were the only significant variables included in the discriminant analysis. Cross-validation results showed that 17 of 19 selected players (89.5%) and 5 of 9 non-selected players (55.6%) were correctly classified into selected and non-selected groups, respectively, providing an overall predictive accuracy of 78.6%. The results of this study demonstrate that selected skill test results (i.e. subjective coach evaluations of passing technique and serving technique), but not physiological and anthropometric data, discriminate between successful and unsuccessful talent-identified junior volleyball players. These results demonstrate the importance of developing passing and serving technique in talent-identified junior volleyball players.